Penerapan Teknologi Tepat Guna Padi Sawah Spesifik Lokasi di Dusun Ponggok, Trimulyo, Jetis, Bantul - Sri Nuryani Hidayah Utami; Achmadi Priyatmojo; Subejo Subejo (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
The role of technology is very important in supporting improvement of agricultural production. The high-tech strategic role was demonstrated by the success in achieving increased production of rice within the last 35 years is the contribution of the application of more advanced technology. Mosher et al. (2003) put technology as an essential condition for agricultural development. If there is no change in the technological development of agriculture was halted. Production halted the increase, it may even decline because of declining fertility tannic or because of damage increased by pest play an increasingly rampant. A view to changing the technology, can be interpreted as an adaptive technology on the condition of the biophysical and social environment of the local culture. Practical application of specific technologies by farmers, for example how farmers adjust to the conditions of cultivation of local agro-ecosystem forming a specific production system on irrigated land, rainfed lowland, upland, swampy areas, and tidal. Choice according to agro-ecosystem farmers are adapting cultivation is calibration-specific technologies. It’s caused each commodity grows well on climatic conditions, soil and culture-specific social support. Community service activities has been implementing the specific technology that is enriched with appropriate technology research team of the Faculty of Agriculture of UGM by utilizing site-specific conditions of Ponggok Hamlet, Trimulyo, Jetis, Bantul, which have ingredients that can be used for making fertilizer and also wisdom locations in rice cultivation which has been done by farmers for generations. Community Service Team of Faculty of Agriculture, UGM during 2013-2015 had engaged in community service based on the results of research and appropriate technologies in Ponggok Hamlet, for 2 seasons seen significant progress and participation of farmers. In 2013 the results of the demonstration plot tile average of 6.8 tons/ha, after continuous mentoring and counseling in 2014 the results of tile becomes 7.8 to 9.8 tons/ha. Activities application of appropriate technology in a farmer’s land is not easy. Although guidance and counseling has been done before, but not all farmers want and dare to carry out all of the technology that is recommended because it is still in doubt, especially with regard to plant spacing, seed age and the number of seedlings planted. In 2015, a technology package has been introduced covering healthy seedlings, planting system “footprint tiger”, “tajarwo”, homemade compost with waste around the site and biological fertilizers. The results of the application of specific technologies in the growing season of April to July 2015 showed an increase in rice production, but the farmer as a principal factor remains the key to successful application of the technology.